Betablockers reduce oxygen pulse increase and performance in heart failure patients with preserved ejection fraction. (1st January 2023) - Wernhart, Simon; Papathanasiou, Maria; Mahabadi, Amir Abbas; Rassaf, Tienush; Luedike, Peter
Abstract: Background: Beta blockers (BB) reduce chronotropic response and exercise capacity in heart failure with preserved ejection fraction (HFpEF). To analyze the influence of BB on exercise performance and O 2 pulse increase as a surrogate for stroke volume in HFpEF. Methods: We retrospectively analyzed the influence of BB intake (yes: n  = 48/no: n  = 51) on peak oxygen uptake (VO 2peak), oxygen uptake efficiency slope (OUES), and increase of O 2 pulse in HFpEF patients undergoing cardiopulmonary exercise testing (CPET). Associations of outcome variables and risk category of the algorithm of the Heart Failure Association of the European Society of Cardiology (HFA-PEFF score) were calculated. Results: Patients on BB showed lower VO 2peak ( p  = .003) and OUES ( p  = .002), with a dominant effect in the high-risk ( p  = .020; 0.002), but not in the low risk-group ( p  = .434; p  = .499). In the intermediate group BB showed a trend towards lower VO 2peak ( p  = .078) and lower values for OUES ( p  = .020). Patients on BB also demonstrated a lower increase of O 2 pulse during exercise ( p  = .002), without differences between HFA-PEFF risk groups (low: p  = .322, intermediate: p  = .269, high: p  = .313). Conclusions: BB reduce exercise capacity and O 2 pulse increase in HFpEF patients. Direct quantification of O 2 pulse increase may help to improve the discrimination of HFpEF patients. Graphical abstract: Unlabelled Image Highlights: BB intake is associated with reduced exercise capacity in HFpEF patients. BB intake reduces O2 pulse increase as a surrogate for blunted stroke volume. BB should be avoided in selected HFpEF patients. Cardiopulmonary exercise testing contributes to characterize HFpEF phenotype